RESULTS OF EXPLOITATION OF CRYSTALLIZERS SLEEVES CONSTRUCTION «VM-SINUS» ON PROFILED MACHINES OF BILLETS CONTINUOUS CASTING OF RUP «BMZ» - A. V. Demin (Литьë и металлургия, 2011)
The results of introduction of sleeves of crystallizers of construction «Vm-sinus», produced in conditions of the Belorussian metallurgical works on the technology developed in AHK BNIIMETMASh, are considered.